Effect of addition of pro-enzymes and Spirulina flour on growth and color intensity of betta fish (Betta sp). Issue 1 (October 2021) - Fabanjo, M A; Abdullah, N
Abstract: Betta fish is one of the ornamental fish that has high economic value because it has features such as the beauty of the body color, the uniqueness of the shape of the fins so that it is very attractive to ornamental fish lovers. Attractiveness value of ornamental fish can be measured from their brilliant color, shape and physical completeness, behavior, and health conditions. Color is one deciding factor that ornamental fish is in demand by consumers, so that farmers need to maintain the color of ornamental fish by providing food containing color pigments. The aim of this study was to obtain a mixture of effective doses of pro-enzyme Spirulina flour in feeding to increase growth and color intensity of betta fish. The results showed that the highest absolute weight growth was found in treatment B (5 grams) of pro-enzyme Spirulina flour 2.154 followed by treatment C 1.554 (7 grams), treatment A 0.844 (3 grams), and treatment D 0.002 (0 grams). The highest level of color change occurred in treatment A (dose of 3 grams) while the lowest color change rate was found at treatment D (0 grams).